2020
DOI: 10.1158/1538-7445.sabcs19-ot2-01-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract OT2-01-05: A prospective real-world national study to evaluate the efficacy and safety of adjuvant biosimilar trastuzumab in the treatment of HER2-positive breast cancer

Abstract: Background: Treatment with anti-HER2 therapy significantly improved survival outcomes in patients with HER2-positive Breast Cancer (BC). In Brazil, Trastuzumab was the first biosimilar approved in the treatment of patients with breast (any disease setting) and advanced gastric cancer with overexpression of HER2. Increase access to this important treatment may be enhanced with biosimilar approval. The aim of this Real-World study is to assess the efficacy and safety of adjuvant biosimilar trastuzumab in Brazili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…The same study reported better survival outcomes in patients with EBC or MBC who received treatment with RTZ, illustrating how the high cost of RTZ can deprive patients of effective treatments. As in previous studies (8,31,32), the results of this study also suggest that biosimilar trastuzumab may provide treatment as safe and effective as RTZ, but at a remarkably presented opportunity for cost-saving and thereby to improved access for patients of HER2 positive breast cancer.This real-world study suggests that the biosimilar CT-P6 has similar effectiveness and cardiac safety to RTZ in HER2-positive EBC and MBC, when administered as part of dual HER2-targetd therapy with pertuzumab and chemotherapy in the neoadjuvant or palliative first-line setting. CT-P6 was well tolerated, with a cardiac safety profile similar to that of the RTZ.…”
Section: Discussionsupporting
confidence: 79%
“…The same study reported better survival outcomes in patients with EBC or MBC who received treatment with RTZ, illustrating how the high cost of RTZ can deprive patients of effective treatments. As in previous studies (8,31,32), the results of this study also suggest that biosimilar trastuzumab may provide treatment as safe and effective as RTZ, but at a remarkably presented opportunity for cost-saving and thereby to improved access for patients of HER2 positive breast cancer.This real-world study suggests that the biosimilar CT-P6 has similar effectiveness and cardiac safety to RTZ in HER2-positive EBC and MBC, when administered as part of dual HER2-targetd therapy with pertuzumab and chemotherapy in the neoadjuvant or palliative first-line setting. CT-P6 was well tolerated, with a cardiac safety profile similar to that of the RTZ.…”
Section: Discussionsupporting
confidence: 79%
“…A study conducted in China showed that the use of RTZ is higher in rich countries than in poor countries, and accordingly, survival is better in both the early and metastatic stages [28]. As in previous studies [1,11,26,29], our study has shown that biosimilar drugs are as effective and safe as RTZ. In this way, drug-expenditure will decrease and access to effective treatments will be easier.…”
Section: Discussionsupporting
confidence: 82%